Poisonous insects - Bender, Lionel; Thompson, George, 1944- (New York : Gloucester Press, 1988)
A study of insects that cause harm or damage to other animals or plants. Explains where the insects live, what they look like, and how they survive.
Includes index.
Booklist
6.5
3-6
Keywords: Insects -- Juvenile literature; Insect pests -- Juvenile literature; Arthropoda, Poisonous -- Juvenile literature; Insects; Insect pests; Arthropods, Poisonous; Poisonous animals; Insects, Injurious and beneficial